TEORI TRANSAKSI ROSENBLATT DAN IMPLEMENTASINYA DALAM PENGAJARAN SASTRA - Azhariansah, Azhariansah (Universitas Ahmad Dahlan, 2015)
Transaction theory is an idea approach of literature teaching developed by Louise Michelle Rosenblatt. This Theory was recommended to be use at students whose age 4-12 year or elementary school level, but it can be used for higher level. Transaction theory portray the existence of interrelationship (reciprocal) between art text and student. Assumption of transaction theory in literature teaching is meaning of literature is created by reading activity, students early respons have to consider, class atmosphere has to co-operative, related to daily life, and linkage with other literatures.